The hidden cost of private health insurance in Australia - Seah, D.; Cheong, T.; Anstey, Matthew (2013)
The provision of health services in Australia currently is primarily financed by a unique interaction of public and private insurers. This commentary looks at a loophole in this framework, namely that private insurers have to date been able to avoid funding healthcare for some of their policy holders, as it is not a requirement to use private insurance when treatment occurs in Australian public hospitals. © AHHA 2013.